2022
DOI: 10.1155/2022/9030771
|View full text |Cite
|
Sign up to set email alerts
|

HBO Alleviates Neural Stem Cell Pyroptosis via lncRNA-H19/miR-423-5p/NLRP3 Axis and Improves Neurogenesis after Oxygen Glucose Deprivation

Abstract: Due to the limited neurogenesis capacity, there has been a big challenge in better recovery from neurological dysfunction caused by stroke for a long time. Neural stem cell (NSC) programmed death is one of the unfavorable factors for neural regeneration after stroke. The types of death such as apoptosis and necroptosis have been deeply investigated while the pyroptosis of NSCs is not quite understood. Although it is well accepted that hyperbaric oxygen (HBO) alleviates the oxygen-glucose deprivation (OGD) inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The NLRP3‐dependent pyroptosis signaling was silenced as a result of the inhibition of the lncRNA‐H19/miR‐423‐5p/NLRP3 axis, which was the underlying mechanism. The findings increased our comprehension of NSC pyroptosis and offered a fresh idea for developing a treatment plan for stroke‐induced neuronal regeneration 139 . LncRNA‐ZFAS1 overexpression reduced m6A levels of Drp1 and undid the exosomal KLF4 silencing's positive effects on mitochondrial damage and the imbalance of mitochondrial dynamics.…”
Section: Mirna and Lncrna‐based Delivery By Stem Cells In Strokementioning
confidence: 85%
“…The NLRP3‐dependent pyroptosis signaling was silenced as a result of the inhibition of the lncRNA‐H19/miR‐423‐5p/NLRP3 axis, which was the underlying mechanism. The findings increased our comprehension of NSC pyroptosis and offered a fresh idea for developing a treatment plan for stroke‐induced neuronal regeneration 139 . LncRNA‐ZFAS1 overexpression reduced m6A levels of Drp1 and undid the exosomal KLF4 silencing's positive effects on mitochondrial damage and the imbalance of mitochondrial dynamics.…”
Section: Mirna and Lncrna‐based Delivery By Stem Cells In Strokementioning
confidence: 85%
“…This results in an impairment of neuronal function in MS [ 73 ]. Downregulation in preterm versus term mature milk is the same way for miR-423-5p, which is known that acts repressing neurogenesis [ 74 ], and also tissue fraction of major depressive disorder (MDD) subjects in the synaptic fraction is upregulated [ 75 ]. On the other hand, miR-451a, which has lower levels in late preterm than in term mature milk, was downregulated in AD cerebrospinal fluid (CSF) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs act as key regulators of pyroptosis by modulating the expression levels of key genes in pyroptosis. [44][45][46] EZH2 was shown to suppress the expression of microRNAs under oxidative stress, such as miR-139, 47 miR-34a 35 and miR-451. 48 Recently, miR-22 was reported to promote endothelial cell pyroptosis.…”
Section: Discussionmentioning
confidence: 99%